Persistent Tachypnea and Alveolar Hemorrhage in an Infant: An Unexpected Etiology - John Bishara; Angela Webb; Christina Valsamis; Claudia Halaby; Melodi Pirzada (Hindawi Limited, 2016)
Persistent tachypnea and failure to thrive during infancy have a broad differential diagnosis which includes pulmonary and cardiovascular disorders. Diffuse alveolar hemorrhage (DAH) is a rare entity in children. DAH requires an extensive work-up as certain conditions may need chronic therapy. Cardiovascular disorders are included in the etiology of DAH. We present a case of an 8-month-old female with a moderate, restrictive patent ductus arteriosus (PDA) admitted to the hospital with respiratory distress and failure to thrive. An extensive work-up into tachypnea including multiple echocardiograms did not find an etiology. Open lung biopsy was performed and consistent with pulmonary hypertension. After closure of the PDA, patient's tachypnea improved, and she was discharged home with periodic follow-up showing a growing, thriving child. When an infant presents with tachypnea, a respiratory viral illness is often a common cause. The diagnosis of persistent tachypnea requires further investigation. Echocardiography, although readily available, may not always be sensitive in detecting clinically significant pulmonary hypertension. A clinician must have a heightened index of suspicion to proceed in evaluating for causes of tachypnea with a nonrespiratory etiology.